The beliefs of health workers in occupational accidents with exposure to biological fluid: descriptive research - Wall, Marilene Loewen; Miranda, Fernanda Moura D'almeida; Sarquis, Leila Maria Mansano; Labronici, Liliana Maria; Cruz, Elaine Drehmer de Almeida (Online Brazilian Journal of Nursing, 2011)
It is descriptive quantitative and qualitative approach performed between September and October 2010 with 15 health workers. Objective- To identify the knowledge about the consequences of exposure to biological material, and the protocol of post-accident, and know beliefs that influence this adherence. Methods- The data were collected through structured interview recorded and analyzed using thematic analysis. Results- The workers are concerned about contracting AIDS and hepatitis, related preventive behaviors add to the risk after the event, the serological follow perceive as a benefit, they recognize the accident as a generator of emotional stress and reported no investments of institutions to promote awareness and prevent accidents biological exposure. Conclusion- The nursing consultation to the rugged provides subsidies through health education for behavior change and helps to improve the quality of life of the worker.